الزيتون في القرآن الكريم : دراسة صرفية - دلالية - الحمداني، خديجة زبار عنيزان; الشجيري، ابتسام عباس (ديوان الوقف السني - مركز البحوث والدراسات الاسلامية, 2009)
There are Qoranic verses told by God about nature, a wonderful world. Botany has more than 100 marks. About Olives There are 7 places (studies derivation) syboawah neglected among building and its evidence limited to location and classification depending on verse on it.
Keywords: بلاغة القرآن -- ألفاظ القرآن -- الزيتون -- اللغة العربية -- الصرف -- تفسير القرآن -- نحو القرآن -- شجرة الزيتون